Artificial Intelligence and Its Misuse in Crime: Emerging Legal and Ethical Concerns in the Digital Age - Acharya, Subash (Nepalese Journal of Management Science and Research, 2026)
Artificial Intelligence (AI) has become a focus for modern criminal justice systems, offering new capabilities in investigation, digital forensics, and judicial decision-making. Yet these same technologies are increasingly misused for cyberattacks, deepfakes, identity theft, automated fraud, and data manipulation, creating complex legal and ethical challenges. This paper examines the dual role of AI and analyses emerging concerns related to criminal attribution, evidentiary reliability, privacy, and algorithmic bias. It draws on key international frameworks including the UNODC guidelines on AI and criminal justice (2023), the Council of Europe’s Framework Convention on AI (2024 draft), the EU AI Act (2024), and the OECD AI Principles (2019) to highlight global governance efforts. Comparative insights from State v. Loomis (USA), ECtHR jurisprudence, and predictive policing practices in the UK, India, and Nepal further demonstrate both opportunities and risks. The study employs a mixed-method research design combining quantitative data, doctrinal legal analysis, and comparative assessment to evaluate AI’s implications for Nepal’s criminal justice system. Overall, the paper underscores the need for ethical, accountable, and rights-based AI governance to ensure fairness and sustainability in criminal justice.